Eastern Asia : Sino‐Tibetan linguistic history - LaPolla, Randy J. (Wiley-Blackwell, 2021)
The Sino‐Tibetan language family enshrines the migratory histories of many East Asian populations, including the Chinese, Tibetans, and Burmese. Its history is intimately associated with Neolithic and Bronze Age developments in China itself, and today it is one of the major world language families in terms of population numbers.